Meningkatkan Aktivitas dan Hasil Belajar Siswa Muatan IPAS Materi Sistem Pernapasan Kelas V dengan Model Project Team dan Alat Peraga - Lusiana .; Sakerani . (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The aim of PTK is to describe teacher activities and analyze the increase in student activity and learning outcomes using the project team model (Project Based Learning, Teams Games Tournament and Mind Mapping) and teaching aids in the science content material on the respiratory system in humans. The subject of this research was class V at SDN Mawar 7 Banjarmasin with a total of 23 students. The research was carried out in 4 meetings. The results of this research show that teacher activity reached 100% with the criteria "Very Good". Student activity reached a percentage of 91% with the criteria "Very Active". Student learning outcomes have increased with the percentage of classical completion reaching 91% of students who completed. Based on the results of this research, it is recommended for teachers to use a project team model and teaching aids for the human respiratory system in class V to be able to increase learning activities which also have an impact on increasing student learning outcomes.